2016
DOI: 10.5301/ijao.5000480
|View full text |Cite
|
Sign up to set email alerts
|

Apically Extruded Debris during Root Canal Preparation using ProTaper Gold, ProTaper Universal, ProTaper Next, and RECIPROC Instruments

Abstract: All systems caused apical debris extrusion during curved canal preparations. However, the PTG, PTN, and RECIPROC systems resulted in significantly less debris extrusion than the PTU system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 20 publications
(27 reference statements)
3
20
0
Order By: Relevance
“…Three articles on molars were selected for this review. In these articles, the Reciproc system showed lower apical extrusion of debris [ 49 , 50 ]; however, in the study by Kuştarcı et al , there was no statistically significant difference between the Reciproc and TFA systems evaluated in premolars [ 51 ].…”
Section: Apical Extrusion Of Debrismentioning
confidence: 99%
“…Three articles on molars were selected for this review. In these articles, the Reciproc system showed lower apical extrusion of debris [ 49 , 50 ]; however, in the study by Kuştarcı et al , there was no statistically significant difference between the Reciproc and TFA systems evaluated in premolars [ 51 ].…”
Section: Apical Extrusion Of Debrismentioning
confidence: 99%
“…Other studies have demonstrated a change in the surface of rotary instruments after use ( 8 ). Although many previous studies have investigated various aspects of the ProTaper Next™ and ProTaper® Universal files, which include canal shaping ability ( 9 ), cyclic fatigue resistance ( 10 ), amount of debris extruded ( 11 ) etc., no studies have investigated how the surface and the alloy features would affect instrument fracture. Hence, the aim of this study was to analyze surface irregularities of these two rotary files before use and after instrumentation in curved canals in extracted human teeth.…”
Section: Introductionmentioning
confidence: 99%
“…5 According to the literature, all instrumentation techniques exhibit some degree of apical extrusion of debris during treatment, however the amount of extruded product will vary depending on the used instrument. 12, 16,18,20 Therefore, the present study aimed to evaluate which rotary instrumentation technique leads to the greatest amount of extruded apical debris, using two different systems instrumentation (Protaper Universal and Protaper Next).…”
Section: Discussionmentioning
confidence: 99%